Multi-model Ensemble Approach for the Assessment of Climate Change Impacts on Water Resources - Islam, Syed Ataharul (Curtin University, 2017)
This research investigates the impact of climate change on water resources using a multi-model ensemble approach through rainfall-runoff projection for A2 and B1 emission scenarios of IPCC (AR4) for mid (2046-2065) and late (2081-2100) century in selected catchments of Western Australia. A bias correction method is also developed to correct projected runoff and a framework for extended hydrologic prediction (EHP) system is outlined. The findings are expected to be beneficial for planning future water resources.